?-ALMOST STATISTICAL CONVERGENCE OF ORDER ? - Colak, R.; Altin, Y.; Et, M. (Univ Al I Cuza, Fac Math, 2014)
In this paper, we introduce the concept lambda-almost statistical convergence of order alpha. Also some relations between lambda-almost statistical convergence of order alpha and strong ((V) over cap, lambda)-almost summability of order alpha are given. Furthermore some relations between the space [(V) over cap (alpha)(p), lambda, f] and (S) over cap (alpha)(lambda) are examined.
Keywords: statistical convergence; almost convergence; Cesaro summability